2009
DOI: 10.1007/s12975-009-0001-0
|View full text |Cite
|
Sign up to set email alerts
|

Treatment with the Iron Chelator, Deferoxamine Mesylate, Alters Serum Markers of Oxidative Stress in Stroke Patients

Abstract: The iron chelator, deferoxamine mesylate (DFO), has shown neuroprotective effects, mediated via suppression of iron-induced hydroxyl radical formation, in various animal models of ischemic and hemorrhagic stroke. Therefore, the objective of this study was to investigate whether DFO can exert similar actions in stroke patients, by examining the effects of treatment with DFO on biological markers of oxidative stress, namely serum total hydroperoxides and lipoperoxides and total radical trapping antioxidant capac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 25 publications
(10 citation statements)
references
References 26 publications
0
10
0
Order By: Relevance
“…One preliminary study on three ischemic stroke cases and four hemorrhagic stroke cases has shown that DFO treatment (500 mg per day for 3 days) is associated with lower serum levels of hydroperoxides and lipoperoxides. 423 Unfortunately, a phase II clinical trial entitled "Thrombolysis and Deferoxamine in Middle Cerebral Artery Occlusion" was completed in 2012 without the results being released (ClinicalTrials.gov identifier: NCT00777140). Thus, carefully designed large-scale studies are warranted to assess the safety and efficacy of iron chelation therapy in stroke patients.…”
Section: Targeting Ferroptosismentioning
confidence: 99%
“…One preliminary study on three ischemic stroke cases and four hemorrhagic stroke cases has shown that DFO treatment (500 mg per day for 3 days) is associated with lower serum levels of hydroperoxides and lipoperoxides. 423 Unfortunately, a phase II clinical trial entitled "Thrombolysis and Deferoxamine in Middle Cerebral Artery Occlusion" was completed in 2012 without the results being released (ClinicalTrials.gov identifier: NCT00777140). Thus, carefully designed large-scale studies are warranted to assess the safety and efficacy of iron chelation therapy in stroke patients.…”
Section: Targeting Ferroptosismentioning
confidence: 99%
“…Early reperfusion is the most effective therapy for acute cerebral ischemia; however, the increase in ROS and inflammation, and other phenomena in tissues after reperfusion aggravates brain tissue damage [ 88 ]. Several studies have indicated that iron chelators attenuate brain injury induced by ischemic stroke in animal models [ 89 , 90 ] and play an antioxidant, neuroprotective role in stroke patients [ 91 ]. Recent studies have suggested that ferroptosis plays a significant role in ischemic stroke [ 92 94 ].…”
Section: Pathological Mechanisms and Potential Targeted Therapy Of Ferroptosis In Ischemia-reperfusion Injurymentioning
confidence: 99%
“…Therefore, protection of neurons in the ischemic penumbra is critical for the treatment of ischemic stroke. Along with the other types of cell death, ferroptosis plays an important role in the pathogenesis of brain ischemia ( Hanson et al, 2009 ; Selim, 2010 ). A detailed account of the chemical biology of ferroptosis in the central nervous system has been well summarized by Ratan (2020 ).…”
Section: Mechanisms Of Ferroptosis In the Pathogenesis Of Ischemic Strokementioning
confidence: 99%